Transformasi Manajemen Madrasah - Barnawi Barnawi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: Madrasah as an Islamic education institute occupies a strategic position in the intellectual life of the nation's effort. Unfortunately, such a strategic position hasn't been fullly utilized so far. The indicators are madrasah has not been the first choice if primary and community education service users. The cause is that the madrasah has not shown a capacity as a good quality institution in a competitive and comparative ones. Transformation of madrasah management can refer to two fundamental queations that is what is doing wrong and what action needs to be done to make better madrasah. From the tranformation carried out, the aim is madrasah institutions that have brand in the hearts of the people. By the brand, the madrasah is expected to be first and foremost choice of the community education service users. Keywords: Transformation and Madrasah Management.